Entre a laguna e o oceano: histórias de um futebol - Cunha, Leonardo Costa da (2012)
With my personal relation with the object of study, added to the concerns of researcher, the dissertation Entre a Laguna e o Oceano: histórias de um futebol tries to understand how the amateur soccer was settled, as well as the meaning of this soccer to the local comunity. This study was elaborated through two articles that, even they complement each other, are independent. The first one, named Outros tempos, outro futebol: o campeonato amador de São José do Norte , talks about the historical events of the amateur soccer league city of São José do Norte, city located on the southern coast of Rio Grande do Sul Brazil. This one talks about the events since the first championship, in 1959, until the year of 2011, showing the social relations created by the amateur soccer clubs in their comunities, as well as the economic influence, both the peak and in decline of the city soccer and the insertion of players from other cities in the local soccer. The second article, named De um clube comunitário a um time vencedor: as relações sócio/históricas do Sport Club Barrense , talks about the history of the oldest football club in activity of the city. Founded in October 18th, 1931, S.C Barrense belongs to Povoação da Barra locality, which is characterized as a fishermen comunity, 16km distant from the city center of São José do Norte. Analyzing its 80 years of history the study shows two distinct phases of the club: from an entity with a strong social appeal in the comunity to the 80‟s, the club starts, from de 90‟s on, to prioritize the creation of competitive teams to the dispute of the amateur championship football, reinventing its relationship with the community